HUBUNGAN DUKUNGAN SOSIAL ORANG TUA DENGAN RESILIENSI AKADEMIK MAHASISWA TINGKAT AKHIR DI UNIVERSITAS X - Cecilia , Cecilia; Suryadi , Denrich (Provitae: Jurnal Psikologi Pendidikan, 2024)
Students carrying out lectures will certainly experience academic challenges and demands, especially final year students. Academic challenges and demands faced include social adjustment, course learning, time management, and organizational tasks. Academic challenges and demands can trigger stress due to poor time management in completing assignments, lack of self-control and a feeling of anxiety about the pressure experienced. In facing challenges, there are students who have academic resilience within themselves and there are also students who do not have academic resilience within themselves. Academic resilience is the internal capacity to face difficulties that will become a major threat to the student's education. One of the supporting factors for the formation of academic resilience is parental social support. Parental social support is a helping hand from parents in the form of emotional, informative, instrumental support, appreciation which illustrates the bond between parents and children. The social support parents provide to children can provide a sense of security and comfort in facing every challenge they are facing. This research aims to determine the relationship between parental social support and academic resilience in final year students at University X. The participants in this research were 313 final year students at University X. This research collects quantitative correlational data using a questionnaire. The measuring instruments used in this research are the Social Provisions Scale (SPS) and The Academic Resilience Scale-30 (ARS-30). The results of correlation data analysis in this study showed a positive and significant correlation (r = 0.740 and p<0.05) between parental social support and academic resilience.